Catalytic Co‐Conversion of CH4 and CO2 Mediated by Rhodium–Titanium Oxide Anions RhTiO2−. Issue 25 (17th May 2021) - Yang, Yuan; Li, Ya‐Ke; Zhao, Yan‐Xia; Wei, Gong‐Ping; Ren, Yi; Asmis, Knut R.; He, Sheng‐Gui
Abstract: Catalytic co‐conversion of methane with carbon dioxide to produce syngas (2 H2 +2 CO) involves complicated elementary steps and almost all the elementary reactions are performed at the same high temperature conditions in practical thermocatalysis. Here, we demonstrate by mass spectrometric experiments that RhTiO2 − promotes the co‐conversion of CH4 and CO2 to free 2 H2 +CO and an adsorbed CO (COads ) at room temperature; the only elementary step that requires the input of external energy is desorption of COads from the RhTiO2 CO − to reform RhTiO2 − . This study not only identifies a promising active species for dry (CO2 ) reforming of methane to syngas, but also emphasizes the importance of temperature control over elementary steps in practical catalysis, which may significantly alleviate the carbon deposition originating from the pyrolysis of methane. Abstract : The catalytic co‐conversion of CH4 and CO2 to syngas mediated by single Rh atom‐doped titanium oxide anions (RhTiO2 − ) has been experimentally identified. The production of free 2 H2 +CO and an adsorbed CO (COads ) could be achieved at room temperature while the only elementary step that requires the input of external energy is desorption of the COads from RhTiO2 CO − .